Glass Stiffness Contribution of Flat and Curved Cable-net Supported Glass Façade Systems - Mustafasanie M. Yussof; Gerard Parke; Mohd Khairul Kamarudin (Institut Teknologi Sepuluh Nopember, 2017)
Glass used in building facade presents an aesthetic feature as well as contributes to the structural stiffness of the whole structural system of the building. In this research, the contribution of glass on the stiffness of the cable-net supported glass facade systems was investigated via experiments. Two generic configurations of cable-net system were considered, namely flat and curved cable-net system, both with and without glass panes. Each system was subjected to static load. The results indicated that the introduction of certain level of curvature to the cable net structure has increased the stiffness of the cable net structure by 11.5%. The glass panes made significant contributions to the stiffness of the whole structural system. The glass stiffness contribution for flat cable-net system was high at the early stage of loading (approximately 40%) but reduced when the load was increased. However, the glass stiffness contribution for curved cable-net increased gradually as the load was increased. For both configurations, the glass stiffness contribution remained steady at about 18% of the whole structural stiffness as the cables in the cable-net stiffened up to the maximum load.. Based on the static tests carried out, the pre-stress force in the cables in the cable-net systems can possibly be reduced should the glass be considered in the analysis design of cable-net structure. Moreover, the curved cable-net could be designed to have lower pre-stress force in cables compared to that of flat cable-net to meet the deflection criterion of the cable-net structure.